Surface Display of Recombinant Proteins on Bacillus subtilis Spores - Isticato, Rachele (American Society for Microbiology, 2001)
We developed a novel surface display system based on the use of bacterial spores. A protein of the Bacillus subtilis spore coat, CotB, was found to be located on the spore surface and used as fusion partner to express the 459-amino-acid C-terminal fragment of the tetanus toxin (TTFC). Western, dot blot and fluorescent-activated cell sorting analyses were used to monitor TTFC surface expression on purified spores. We estimated that more than 1.5 × 10(3) TTFC molecules were exposed on the surface of each spore and recognized by TTFC-specific antibodies. The efficient surface presentation of the heterologous protein, together with the simple purification procedure and the high stability and safety record of B. subtilis spores, makes this spore-based display system a potentially powerful approach for surface expression of bioactive molecules.